A Bio-Inspired Free-Standing Film with Versatility From Heterogeneous CTCs Programed Isolating to Breast Cancer Molecular Typing - Bai, Mengqi (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.